Meta-Analysis of Mixed Sowing Effects on Forage Yield and Water Use Efficiency in China: Influencing Factors and Optimal Conditions - Weiqiang Guo; Yuanbo Jiang; Minhua Yin; Yi Ling; Yanxia Kang; Guangping Qi; Yaya Duan; Yanlin Ma; Yushuo Liu; Gen Ling; Kaili Pan (Plants)
Mixed sowing of forage grass can reduce soil erosion, improving forage nutritional composition, enhancing grassland productivity, and increasing community stability. It addresses issues faced by sown pasture, including a lack of diversity in planting patterns, low resource utilization efficiency, and poor sustainability. However, the effects of mixed sowing on forage yield and water use efficiency (WUE) vary depending on regional environmental conditions, management practices, and temporal factors. Based on publicly available field experiment data, this study utilized meta-analysis to quantitatively examine the effects of mixed sowing on forage yield and WUE in China. Additionally, a random forest model was employed to analyze the main influencing factors. The results showed that, compared with monoculture, mixed sowing significantly improved forage yield and WUE, with average increases of 58.3% (confidence interval: 44.3–72.3%) and 32.0% (confidence interval: 19.2–44.8%), respectively. Regarding yield, the effect of mixed sowing was the most pronounced in Shaanxi. Optimal conditions included experiments conducted during 2006–2008, annual precipitation of 200–600 mm, soil pH of 4−5, average annual temperature of 10–15 °C, altitudes below 2000 m, alfalfa (Medicago sativa) and Bromus inermis as the forage combination, two species in the mixture, a legume-to-grass species ratio of 1:1, a total seeding rate of 40–50 kg·ha−1, and mixed sowing in the same row. For WUE, significant effects were observed in Gansu under the following conditions: experiments conducted during 2018–2020, annual precipitation of 400–600 mm, an average annual temperature of 5–10 °C, a soil pH of 8–9, altitudes of 1000–2000 m, oats (Avena sativa) and peas (Pisum sativum) as the forage combination, two species in the mixture, a legume-to-grass species ratio of 1:1, a total seeding rate of <50 kg·ha−1, and mixed sowing in alternate rows. The random forest model indicated that the effects of mixed sowing on forage yield were primarily influenced by annual precipitation, average annual temperature, and experimental region. In contrast, the effects on WUE were mainly determined by forage combination, species type, and the legume-to-grass species ratio. This study provides a reference for enhancing alfalfa productivity and achieving efficient water use.